Molecular Docking Study of Conformational Polymorph: Building Block of Crystal Chemistry - Rashmi Dubey; Ashish Kumar Tewari; Ved Prakash Singh; Praveen Singh; Jawahar Singh Dangi; Carmen Puerta; Pedro Valerga; Rajni Kant (The Scientific World Journal)
Two conformational polymorphs of novel 2-[2-(3-cyano-4,6-dimethyl-2-oxo-2H-pyridin-1-yl)-ethoxy]-4,6-dimethyl nicotinonitrile have been developed. The crystal structure of both polymorphs (1a and 1b) seems to be stabilized by weak interactions. A difference was observed in the packing of both polymorphs. Polymorph 1b has a better binding affinity with the cyclooxygenase (COX-2) receptor than the standard (Nimesulide).